Controllable perfect absorption in a double-cavity photonic crystal with one graphene monolayer. (15th December 2017) - Bian, Li-An; Yang, Liang; Liu, Peiguo; Chen, Yuwei; Liu, Hanqing; Zhou, Qihui
Abstract: Depending on one graphene monolayer solely, two absorption modes are obtained in a double-cavity photonic crystal. The Fabry–Perot (FP) resonance or Fano resonance can be excited in the graphene cavity, while the FP resonance only is enabled in the empty cavity. At each resonance, the perfect absorption is realized in the case of critical coupling. By controlling the chemical potential of graphene, two FP resonance modes can be tuned independently. In the presence of the embedding inaccuracy of graphene, the FP resonance mode is robust and yet the Fano resonance mode behaves more sensitively. By changing the geometries of two cavities, FP–FP resonances or FP-Fano resonances are coupled to generate the peculiar coupling lineshape. Finally, the absorption structure allows to be characterized by perfect absorption, double modes, few graphene, flexible tuning and coupling lineshape.